1992
DOI: 10.1007/bf02399708
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at enzyme loci in North Atlantic minke whales,Balaenoptera acutorostrata

Abstract: Electrophoretic variation within and between North Atlantic minke whale samples (Balaenoptera acutorostrata) from West Greenland, Iceland, and Norway was investigated. In the West Greenland samples, 28 enzyme systems were examined, representing 36 loci, of which 6 were found to be polymorphic. In Icelandic and Norwegian samples, 22 enzyme systems were examined, representing 29 loci, of which 6 and 5 were found to be polymorphic, respectively. The average heterozygosity was 0.058 (SE = 0.024) in samples from We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…One explanation for the finding in the present study of 2 genetically different sub-populations of minke whales in West and East Greenland could be that the minke whales from East Greenland constitute a part of the Central North Atlantic stock or sub-population. This explanation was actually suggested by the analysis of population structure in this study (see 4 below) and also by the results of 2 isozyme studies by Danielsdóttir et al (1992Danielsdóttir et al ( , 1995, who observed significantly different allele frequencies between minke whales from West Greenland and Icelandic waters. The latter group is thought to be a part of the Central North Atlantic sub-population.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…One explanation for the finding in the present study of 2 genetically different sub-populations of minke whales in West and East Greenland could be that the minke whales from East Greenland constitute a part of the Central North Atlantic stock or sub-population. This explanation was actually suggested by the analysis of population structure in this study (see 4 below) and also by the results of 2 isozyme studies by Danielsdóttir et al (1992Danielsdóttir et al ( , 1995, who observed significantly different allele frequencies between minke whales from West Greenland and Icelandic waters. The latter group is thought to be a part of the Central North Atlantic sub-population.…”
supporting
confidence: 71%
“…The average heterozygosity observed at the 16 microsatellite loci (Table 4a,b) found in the present study was considerably higher than the heterozygosity levels obtained from allozyme data. Danielsdóttir et al (1992) examined 36 allozyme loci in a total of 173 minke whales representing the suggested West Greenland, Central, and NE Atlantic sub-populations. The observed heterozygosity (H 0 ) ranged from 0.080 to 0.580 (6 polymorphic loci) in the West Greenland sample, from 0.096 to 0.450 (6 polymorphic loci) in the Central and from 0.083 to 0.417 (5 polymorphic loci) in the NE Atlantic sample (Danielsdóttir et al 1992).…”
Section: Genetic Diversity At the Mtdna And Microsatellite Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional work, however, is needed to establish reference values for hormonal concentrations for the various sexual conditions and categories within this species, not only in blood but also in various tissues already collected. This together with accumulating data and improved understanding of other aspects of the fin whale stocks in the North Atlantic Ocean, such as recent genetic studies (Daníelsdóttir, Duke, Joyce & Arnason, 1991; Árnason, Daníelsdóttir, Spilliaert et al 1992) and tracking experiments (Watkins, Moore, Sigurjónsson et al 1984), will greatly facilitate the assessment of fin whale abundance and productivity in different geo¬ graphical areas and support future surveillance of the stocks.…”
Section: Resultsmentioning
confidence: 95%